PENGARUH PERLAKUAN KOLKISIN PADA BENIH SENGON (Falcataria mollucana Miq.) - Islam, Muhammad Fajar; Anwar, Arniana; Rombe, Yunita Pare (Agroplantae: Jurnal Ilmiah Terapan Budidaya dan Pengelolaan Tanaman Pertanian dan Perkebunan, 2024)
S Sengon (Falcataria moluccana Miq.) is a pioneer tree species that is widely developed in industrial plantation forests and community forests because of its fast growing species. The properties of sengon seeds which are classified as orthodox can decrease their viability and vigor during storage. The colchicine hormone is expected to increase the acceleration of plant growth so that it can increase the success of sengon seed growth. The aim of this research was to see the effect of colchicine treatment on the accelerated growth of sengon seeds. This research was carried out using a Completely Randomized Design (CRD) with one factor, namely colchicine concentration. The concentrations used are: 0 (control), 0.5 ppm, 1.0 ppm, 1.5 ppm, 2.0 ppm. The effect of the treatment was seen through variance testing using SAS 9.0 portable software. The variance results showed that soaking in colchicine solution had a very significant effect on the maximum growth potential, germination capacity and germination value, while the colchicine solution soaking treatment had no real effect on growth speed.